47.0k views
5 votes
Simplify: n(8n−6)+10(7−n)=2

A. 3n²−9n=−48
B. 8n²−16n=−68
C. 8n²−12n=−68
D. −30n²−20n=22

User Tomachi
by
4.8k points

2 Answers

4 votes
i think i’m may be ‘B’ i’m so sorry if i’m incorrect!!
User George Kargakis
by
4.7k points
4 votes

Answer:

B. 8n²−16n=−68

Explanation:

First - Distribute the n & 10

n * 8n & n * -6 = 8n² - 6n

10 * -n & 10 * 7 = -10n +70

Second - Move the 2 by subtracting

8n² - 6n - 10n +70 = 2 -> 8n² - 6n - 10n +70 - 2 = 2 - 2

Third - Combine like terms

-6n - 10n = -16n

70 - 2 = 68

8n² - 16n + 68 = 0

Fourth - Move 68 by subtracting

8n² - 16n + 68 - 68 = 0 - 68

8n² - 16n = -68

User Rasool Ghafari
by
4.8k points